Improvement of Traction Indicators of a Track-Chain Tractor - Salavat Mudarisov; Ilshat Gainullin; Ildar Gabitov; Eduard Khasanov (Communications - Scientific letters of the University of Zilina, 2020)
The aim of this research was to conduct the comparative traction tests for T-170M1.03-55 tractor with a flat and elliptical rim. Structurally rational geometry of the crawler's support surface for tractors with semi-rigid suspension is realized by placing the support rollers at different heights relative to the cart. The results of traction tests showed that elliptical track rim has increased the maximum traction power by 10.4%, conditional traction propulsive efficiency coefficient to 7.43% and the specific traction effort by 8%. The increase in indicators is provided by a lower rolling resistance of a tractor with an elliptical rim. Reduction of the resistance power to rolling of the tractor with an ellipse track rim occurs due to alignment of support rollers vertical load and reduction of resistance to rollers movement on internal contours of tracks and in hinges of track chain links. The results of the research indicate a significant improvement in traction performance of T-170M1.03.55 tractors with elliptical track-chain rim.